(untitled) (International conference on multidisciplinary science, 2025)
This article examines idiomatic expressions in English and Uzbek languages that describe human character and appearance. The research focuses on identifying the semantic, cultural, and linguistic characteristics of idioms, comparing their usage in both languages, and analyzing their implications in communication and cross-cultural understanding. By providing examples from both languages, the study reveals the cultural similarities and differences in the perception of human traits and physical attributes. The findings emphasize the role of idioms as linguistic tools that reflect a nation’s worldview and identity.